HARMONIZING WAQF AND DIGITAL TRANSACTIONS - Zuchroh, Imama (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The highest form of philanthropy in Islam is waqf, where aspects of worship, legal, social and economic aspects have existed in it. In line with the time of the waqf era, it is not only restricted to immovable objects such as buildings as well as land. But also, in waqf in the form of money. Based on some literature, waqf money has a large and wider impact on society. With the increase in technology in financial activities, e-payments can be used as a means to optimize waqf fund collection, of course as a result of technological advances in the field of finance, this dynamism needs to be studied more deeply. This research uses a qualitative type of research with a literature study model in answering these problems. Data is obtained from various reading sources such as books, previous research, journals, and trusted websites. The essence of this research leads us to the conclusion that electronic transactions or e-payments are proven to help optimize the collection of waqf funds. In the digital era, electronic financial transactions and waqf can be harmonized as a means of facilitating waqf both in terms of mobilization and the number of funds to be donated. And with electronic payments, it will increasingly protect those who waqf more securely, comfortably, and efficiently.